2022
DOI: 10.3390/su142114354
|View full text |Cite
|
Sign up to set email alerts
|

Oasis Change Characteristics and Influencing Factors in the Shiyang River Basin, China

Abstract: The variability of the natural environment and the complexity of human activities result in dynamic changes in oasis areas, which is directly related to the sustainable development of arid and semi-arid areas. In order to better balance economic development and environmentally sustainable development, based on land use data and social and economic data from 1980 to 2015, this paper analyzed the oasis change characteristics under natural and human factors in the Shiyang River Basin in Northwest China. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It was found that the expansion of arable land and construction land is a key factor leading to the ecological decline of the Shule River [28], and this relevant point of view was also confirmed in the Manas River basin [27]. For this reason, artificial oases have been proposed as a key factor leading to the decline in ecological environment quality [2]. In order to prevent ecological degradation, natural oases need to be protected and the continued expansion of artificial oases must be curbed.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…It was found that the expansion of arable land and construction land is a key factor leading to the ecological decline of the Shule River [28], and this relevant point of view was also confirmed in the Manas River basin [27]. For this reason, artificial oases have been proposed as a key factor leading to the decline in ecological environment quality [2]. In order to prevent ecological degradation, natural oases need to be protected and the continued expansion of artificial oases must be curbed.…”
Section: Introductionmentioning
confidence: 90%
“…In the unchanged oasis condition, the area of RSEI increase is only 31.5 thousand, accounting for 16.15% of the total area of the oasis, mostly distributed in the upper and middle reaches of the oasis with better water conditions, which is dominated by the increase in ecological quality of AO, with an area of 22.2 thousand km 2 , and the area of NO is only 0.930 thousand km 2 ; the expansion of the oasis brings about the enhancement of the RSEI, which accounts for 34.3 thousand km 2 , accounting for 0.930 thousand km 2 of the total oasis km 2 , accounting for 17.58% of the total oasis area, with an area of 26,400 km 2 for AO and 0.79 million km 2 for NO. On the contrary, the oasis expansion caused a decrease in the RSEI value of the area of 18.43%, with an area of 14,700 km 2 for AO and 21,200 km 2 for NO, which was mainly distributed in the periphery of the existing oasis, and subject to the resource and environmental constraints. This type of change is mainly distributed in the periphery of the existing oasis, and due to the limitation of resources and environment, the transformation between AO and NO is more frequent, and the ecological quality of the oasis is lower.…”
Section: Characteristics Of Spatial and Temporal Changes In Ecologica...mentioning
confidence: 97%
See 2 more Smart Citations
“…However, since the 1950s, desertification has increased in China, peaking between the 1970s and early 1980s, then later started ecosystem rehabilitation projects [15]. Particularly the Shiyang River Basin, as a pivotal in natural resource reserves in the Hexi Corridor zone, has also been subject to extreme natural and excessive anthropogenic pressures leading to rapid ecological deterioration and desertification at an unprecedented rate [21,22]. For example, temperature increases and reduced glacial meltwater in the Qilian Mountains have led to a water supply shortage for the past few decades [23].…”
Section: Introductionmentioning
confidence: 99%